Efektivitas Endorsement Selebgram: Studi Netnografi pada Akun @kaosnyenyes di Instagram - Cindy . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the effectiveness of celebrity endorsements as a marketing communication strategy for the Kaos Nyenyes brand on the Instagram platform. The method used is a qualitative approach with a netnography method, which allows researchers to observe in depth the communication practices, visual content, and digital interactions that are formed naturally on the @kaosnyenyes account. The results of the study show that celebrity endorsements not only play a role in increasing brand awareness and audience engagement, but also significantly influence purchasing interest through personal narratives, visual evidence, and empathetic interactions in the digital space. The novelty of this research lies in the application of the netnography approach to explore influencer-based marketing strategies for local fashion brands in Indonesia, which has rarely been studied through a naturalistic qualitative approach in the context of the Instagram platform.